2012
DOI: 10.1159/000338113
|View full text |Cite
|
Sign up to set email alerts
|

Dilated Fourth Ventricle in Fetuses with Trisomy 18, Trisomy 13 and Triploidy at 11–13 Weeks’ Gestation

Abstract: Objective: To determine if in fetuses with aneuploidies the diameter of the fourth cerebral ventricle at 11–13 weeks’ gestation is different from euploid fetuses. Methods: The fourth ventricle at 11–13 weeks’ gestation was assessed in 62 cases of trisomy 21, 32 of trisomy 18, 10 of trisomy 13, and 12 of triploidy and compared to 410 normal euploid fetuses. Transvaginal sonography was carried out and 3D brain volumes were acquired. The fetal head was assessed in an axial plane and the diameter of the fourth ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…It was found that, in the diandric type, fetal NT is increased as well as maternal serum total human chorionic gonadotropin (hCG), free β ‐hCG, and AFP with mildly decreased PAPP‐A, while the digynic type is characterized by a normal fetal NT with markedly decreased maternal serum total hCG, free β ‐hCG, and PAPP‐A . However, the sonographic characteristics described in these studies in the first trimester are sparse and non‐specific, such as severe asymmetrical fetal growth restriction . Another disadvantage of the FTS for triploidy is that FTS identifies mostly the diandric type that is less common.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that, in the diandric type, fetal NT is increased as well as maternal serum total human chorionic gonadotropin (hCG), free β ‐hCG, and AFP with mildly decreased PAPP‐A, while the digynic type is characterized by a normal fetal NT with markedly decreased maternal serum total hCG, free β ‐hCG, and PAPP‐A . However, the sonographic characteristics described in these studies in the first trimester are sparse and non‐specific, such as severe asymmetrical fetal growth restriction . Another disadvantage of the FTS for triploidy is that FTS identifies mostly the diandric type that is less common.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies it could also be interesting to compare data from fetuses with increased CSF as observed in Trisomy 18, 13 or others [16] or in the group at high risk for a Dandy-Walker malformation [17] or Blake's pouch cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies had demonstrated that the posterior fossa BSOB diameter and the anteroposterior diameter of the fourth ventricle of the trisomy 18, trisomy 13, and triploid fetuses were significantly longer than the normal fetuses [11]. It was also reported that the BS diameter and BS/BSOB ratio were decreased in axial view of the trisomy 18 and trisomy 13 [21]. In consistent with the previous reports, our study confirmed that the BS and BS/BSOB ratio were significantly lower in trisomy 13, trisomy 18 and monosomy X in comparison with normal fetuses (fig.…”
Section: Discussionmentioning
confidence: 99%